Porcine Derived Ingredients in Cosmetic Products and its Halal Authentication Method within Complex Matrices - Nawwaruddin, Hazza' Hammam; Rohman, Abdul; Laksitorini, Marlyn Dian (Journal of Food and Pharmaceutical Sciences, 2024)
Nowadays cosmetics are an important commodity and the market for halal cosmetics is seeing growth. Cosmetics that contain porcine-derived ingredients are typically the source of halal problems. Gelatin and collagen are porcine derivatives that are extensively used in cosmetics. Hence, verifying the presence of porcine derivatives in cosmetics by developing analytical methods is critical. Despite this urgency, determining porcine-derived components in cosmetics is challenging, since cosmetics are quite complex with variable matrix forms. Moreover, to the best of our knowledge, there are only a few papers on developing porcine derivatives analysis in cosmetic items. This mini-review objective is to depict the current understanding of determining porcine collagen and gelatin in cosmetic matrixes. The findings revealed that the LC-MS/MS method is superior for determining gelatin and collagen sources in complex matrixes due to its sensitivity and accuracy. PCR and ELISA methods have challenges with the marker degradation problem since the derivatives undergo extensive processing conditions, thus lowering the methods’ specificity and sensitivity, especially in complex matrixes. The SDS-PAGE method applications are limited and the method is suitable for a relatively simple matrix. This review highlights findings that support future advancements in cosmetic analysis for halal authentication.